Who is asking about medicinal cannabis in palliative care?. Issue 2 (9th February 2020) - Panozzo, Stacey; Le, Brian; Collins, Anna; Weil, Jennifer; Whyte, Jan; Barton, Michael; Coperchini, Maria; Rametta, Meri; Philip, Jennifer
Abstract: Following legislative changes in the availability and prescribing of medicinal cannabis in Australia, we sought to understand prospectively the nature of information seeking and requests for medicinal cannabis in consultations between palliative care clinicians and patients with cancer. The 104 discussions were overwhelmingly initiated by patients and carers (93%) and were for a variety of symptoms, reflecting high levels of patient interest in the use of medicinal cannabis in cancer.